Problem solving in enzyme biocatalysis - Illanes, Andres; Wilson, Lorena; Vera, Carlos (Chichester, West Sussex, United Kingdom : Wiley, 2013)
'The only book to approach enzyme kinetics with a problem-solving focus, for practical applications in the food, pharmaceutical, and fine chemistry industry'--
Includes index.
Keywords: Enzymes -- Biotechnology; Biocatalysis; Enzyme kinetics; Enzymes -- Industrial applications